Direct prejudgement of hot images with detected diffraction rings in high power laser system. (2018) - Yang, Aihua; Li, Zhan; Liu, Dean; Miao, Jie; Zhu, Jianqiang
Abstract : A direct prejudgement strategy that takes the diffraction ring as the analysis target is put forward to predict hot images induced by defects of tens of microns in the main amplifier section of high power laser systems. Analysis of hot-image formation process shows that the hot image can be precisely calculated with the extracted intensity oscillation of the diffraction ring on the front surface of the nonlinear plate. The gradient direction matching (GDM) method is adopted to detect diffraction rings. Recognition of simulated diffraction rings shows that it is feasible to directly prejudge hot images induced by those closely spaced defects and the defects that are far apart from each other. Image compression and cluster analysis are utilized to optimize the performance of the GDM method in recognizing actually collected diffraction images. Results show that hot images induced by defects of tens of microns can be directly prejudged without redundant information.